2013
DOI: 10.1503/cmaj.130875
|View full text |Cite
|
Sign up to set email alerts
|

Trends in 1-year survival of people admitted to hospital in Ontario, 1994–2009

Abstract: H ospitals have a special place in most health care systems. Hospital staff care for the people with the most serious illnesses and the most vulnerable. They are frequently the location of many life-defining moments -including birth, surgery, acute medical illness and death -of many people and their families. Hospitals serve as a focus in the training of most physicians. In addition, they consume a considerable proportion of health care expenditures worldwide. 1Given the prominence of hospitals in health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…In that study, adults older than 65 years had an associated 6-to 25-fold increased odds of death compared with adults aged 20-25 years. 4 None of these studies measured the risk of death after a first hospital admission (none of the patients in our study had been admitted in the previous 5 years) in a cohort of older adults. Therefore, the findings from these studies may be heavily influenced by patients with multiple comorbidities and repeated hospital admissions, and do not directly apply to a population of healthier people like those in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In that study, adults older than 65 years had an associated 6-to 25-fold increased odds of death compared with adults aged 20-25 years. 4 None of these studies measured the risk of death after a first hospital admission (none of the patients in our study had been admitted in the previous 5 years) in a cohort of older adults. Therefore, the findings from these studies may be heavily influenced by patients with multiple comorbidities and repeated hospital admissions, and do not directly apply to a population of healthier people like those in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In all groups, we also measured the risk of death stratified by 5-year age intervals. 4 We reported a person's cause of death and grouped it according to a modified form of Becker's leading cause of death. 24 Secondary outcomes, which were intended to generate new hypotheses, included risk of death at 5 years using case-mix grouping to categorize admission diagnoses into those managed as a medical or surgical condition; the total number of emergency department visits, hospital admissions and admissions to the intensive care unit (ICU) for each group during the follow-up period; and risk of death at 5 years in a subset with noncancer diagnoses after their first unplanned hospital admission or visit to the emergency department (see Appendix 1, Table S4, for the complete list of diagnoses).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalisation is an important medical encounter that increases the chance of identifying patients in the last year of life. Previous publications have shown that 12-35% of patients admitted to hospital will die within 12 months of admission [8][9][10][11][12]. Mortality risk assessment models for single diagnoses are often used by hospital specialists but are of limited value since most patients are admitted with advanced, long-term conditions which are multimorbid in nature [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications have shown that 12-35% of patients admitted to hospital will die within 12 months of admission. [8][9][10][11][12] Mortality risk assessment models for single diagnoses are often used by hospital specialists but are of limited value since most patients are admitted with advanced, long-term conditions which are multimorbid in nature. 13 Walsch et al 14 reviewed the four widely used tools in General Practice; three of those, the Gold Standards Framework Prognostic Indicator Guidance (GSF-PIG), 15 the Supportive and Palliative Indicators Tool (SPICT) 16 and the Palliative Necessities CCOMS-ICO (NECPAL) 17 have been tested in hospital populations and have been shown to increase early identification of patients, potentially leading to more proactive care of patients who have palliative care needs.…”
Section: Introductionmentioning
confidence: 99%